2019
DOI: 10.1007/s00127-019-01757-z
|View full text |Cite
|
Sign up to set email alerts
|

Personal continuity versus specialisation of care approaches in mental healthcare: experiences of patients and clinicians—results of the qualitative study in five European countries

Abstract: Background The current debate on organisation of the mental health care raises a question whether to prioritise specialisation of clinical teams or personal continuity of care. The article explores the experiences of patients and clinicians regarding specialisation (SC) and personal continuity (PCC) of care in five European countries. Methods Data were obtained via in-depth, semi-structured interviews with patients (N = 188) suffering from mental disorders (F20-49) and with clinicians (N = 63). A maximum varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Likewise, the traditional model also made the supervision of junior doctors and the ward/s more difficult. Klingemann et al (2020) found that a functionally split model of care has benefits, specifically managerial and professional.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Likewise, the traditional model also made the supervision of junior doctors and the ward/s more difficult. Klingemann et al (2020) found that a functionally split model of care has benefits, specifically managerial and professional.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, although the move to a functionally split system has addressed some of the issues evident in inpatient units’ other issues are yet to be addressed or have emerged as a result of system changes. Thus, both systems are differentially beneficial with neither meeting the needs of all stakeholders (Klingemann et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations